2021
DOI: 10.1002/rcm.9101
|View full text |Cite
|
Sign up to set email alerts
|

New Ag3PO4 comparison material for stable oxygen isotope analysis

Abstract: Rationale A silver phosphate reference material (Ag3PO4) for the measurement of stable oxygen isotope compositions is much needed; however, it is not available from the authorities distributing reference materials. This study aims to fill this gap by calibrating a new Ag3PO4 stable isotope comparison material produced by the University of Natural Resources and Life Sciences (BOKU). Methods Aliquots of Ag3PO4 were distributed to four laboratories who frequently measure the δ18O value in Ag3PO4; the University o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…We believe silver phosphate would be a good candidate because it fulfills these requirements. In addition, silver phosphate is a very stable compound, easy to degas and not hygroscopic, featuring additional benefits to use this material as an international reference standard (Fourel et al, 2011; Lécuyer et al, 2007; Watzinger et al, 2021).…”
Section: Future Methodological Advancesmentioning
confidence: 99%
“…We believe silver phosphate would be a good candidate because it fulfills these requirements. In addition, silver phosphate is a very stable compound, easy to degas and not hygroscopic, featuring additional benefits to use this material as an international reference standard (Fourel et al, 2011; Lécuyer et al, 2007; Watzinger et al, 2021).…”
Section: Future Methodological Advancesmentioning
confidence: 99%
“…Calibration was done using the standards IAEA-601, IAEA-602, and NBS 127 (barium sulphate) and the "quality control" using the standard AGPO-SCRI (14.6‰ ± 0.2‰, standard deviation, against 14.58‰ ± 0.13‰ [48]) and NIST SRM 120c (22.9‰ ± 0.2‰ against 21.79‰ ± 0.15‰, [48]). The values obtained by Halas et al [49] and by Watzinger et al [49] for NIST SRM 120c are apparently significantly different (p (same average) < 0.005); it is noteworthy, however, that analyses reported in literature for NIST SRM 120c are largely variable ( [48] and references therein).…”
Section: Oxygen Of the Phosphatementioning
confidence: 80%
“…More recently, Watzinger et al [49] reported oxygen isotope analyses carried out in four different laboratories on a new silver phosphate sample (BOKU Ag 3 PO 4 ) with 13.71‰ ± 0.34‰ (combined standard uncertainty). Calibration was done using the standards IAEA-601, IAEA-602, and NBS 127 (barium sulphate) and the "quality control" using the standard AGPO-SCRI (14.6‰ ± 0.2‰, standard deviation, against 14.58‰ ± 0.13‰ [48]) and NIST SRM 120c (22.9‰ ± 0.2‰ against 21.79‰ ± 0.15‰, [48]).…”
Section: Oxygen Of the Phosphatementioning
confidence: 99%